Dukungan Suami Dan Pola Makan Terhadap Pencegahan Stunting Pada Saat Ibu Hamil Di Kota Depok - Agustina Sari (Direktorat Politeknik Kesehatan Makassar, 2023)
Stunting is a chronic malnutrition problem caused by a lack of nutritional intake due to the provision of food that does not meet basic nutritional needs. The problem of stunting can start when in the womb & you can only see the symptoms experienced when the child is two years old. This study aims to determine the effect of husband's support & diet on stunting prevention in pregnant women in Depok City. Methods: This research is an observational study with a cross-sectional study design, with independent variables, namely husb& support & eating patterns, & the dependent variable, namely stunting prevention in pregnant women. The population in this study were all pregnant women who live in Depok City in December 2022 with a total sample of 396 people. Data collection was carried out by filling out questionnaires & secondary data. The analytical method used was univariate analysis, bivariate analysis using the Pearson correlation test & multivariate analysis using multiple linear regression tests. Results: based on the results of the Pearson correlation test it can be concluded that there is a significant correlation between husband's support for stunting prevention in pregnant women (p=0.001) & there is a significant correlation between diet & stunting prevention in pregnant women (p=0.001). Based on the R Square value from the results of multiple linear regression analysis, it shows that husband's support & diet obtained a number of 0.893, which means that 89.3% of stunting prevention in pregnant women is influenced by husband's support & diet simultaneously. Conclusion: Based on the results of the research analysis, it was concluded that husband's support & eating patterns have an effect on preventing stunting in pregnant women in Depok City.